2020
DOI: 10.1002/jbt.22488
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin decreases insulin secretion by reducing KCa3.1 as a biomarker of pancreatic tumor and causes apoptotic cell death

Abstract: Insulinomas originate from pancreatic β cells and it is the most widely known tumor. Indomethacin is a nonsteroidal anti‐inflammatory drug, which is used for blocking the production of some natural substances that cause inflammation and decrease pain. In this study, I aimed to investigate the effects of indomethacin on rat insulinoma INS‐1 cells. The relationship between cell death and insulin metabolism was determined with the administration of indomethacin. The cell viability by WST‐1; the apoptosis and necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In addition, it has been shown that the K + channel KCNN4, which is activated by Ca +2 , plays a key role in cell proliferation and plays an important role in cell migration in the pancreatic ductal adenocarcinoma cell line (Bonito et al, 2016). In our previous study, we showed that after indomethacin was applied to the cells for treatment in insulinoma tumors, the level of KCNN4 decreased and the tumor progression decreased by the death of the cell (Karatug Kacar, 2020). Within the scope of this study, it was observed that the expression of KCNN4 increased, but there was no change in the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that the K + channel KCNN4, which is activated by Ca +2 , plays a key role in cell proliferation and plays an important role in cell migration in the pancreatic ductal adenocarcinoma cell line (Bonito et al, 2016). In our previous study, we showed that after indomethacin was applied to the cells for treatment in insulinoma tumors, the level of KCNN4 decreased and the tumor progression decreased by the death of the cell (Karatug Kacar, 2020). Within the scope of this study, it was observed that the expression of KCNN4 increased, but there was no change in the protein level.…”
Section: Discussionmentioning
confidence: 99%